2011
DOI: 10.1039/c1cp20929a
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence correlation spectroscopy evidence for structural heterogeneity in ionic liquids

Abstract: In this work, we provide new experimental evidence for chain length-dependent self-aggregation in room temperature ionic liquids (RTILs) using fluorescence correlation spectroscopy (FCS). In studying a homologous series of N-alkyl-N-methylpyrrolidinium bis(trifluoromethylsulfonyl) imide, [C(n)MPy][Tf(2)N] RTILs of varying alkyl chain length (n = 3, 4, 6, 8, and 10), biphasic rhodamine 6G solute diffusion dynamics were observed; both the fast and slow diffusion coefficients decreased with increasing alkyl chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 38 publications
3
70
1
Order By: Relevance
“…4,5 An important attribute of ionic liquids, which has attracted considerable interest, is their ability to form nanodomains that involve the segregation of local ionic and apolar regions. [6][7][8] Since nanodomains' formation was first noticed via molecular dynamics simulations, [6][7][8] the picture of segregation has been used to explain a variety of experimental data in X-ray scattering, 9,10 dielectric spectroscopy, 11,12 neutron magnetic resonance (NMR) spectroscopy, 10,13,14 fluorescence spectroscopy, [15][16][17] optical heterodyne-detected optical Kerr effect (OHD-OKE) experiments, [18][19][20] and two-dimensional infrared (2D IR) spectroscopy. 21,22 It is important to clarify that not all RTILs have the capability of forming these nanodomains.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 An important attribute of ionic liquids, which has attracted considerable interest, is their ability to form nanodomains that involve the segregation of local ionic and apolar regions. [6][7][8] Since nanodomains' formation was first noticed via molecular dynamics simulations, [6][7][8] the picture of segregation has been used to explain a variety of experimental data in X-ray scattering, 9,10 dielectric spectroscopy, 11,12 neutron magnetic resonance (NMR) spectroscopy, 10,13,14 fluorescence spectroscopy, [15][16][17] optical heterodyne-detected optical Kerr effect (OHD-OKE) experiments, [18][19][20] and two-dimensional infrared (2D IR) spectroscopy. 21,22 It is important to clarify that not all RTILs have the capability of forming these nanodomains.…”
Section: Introductionmentioning
confidence: 99%
“…They found biphasic diffusion dynamics in the ILs, indicating self-aggregation through the alkyl chains. [49] Patra and Samanta also showed, on the basis of their FCS and fluorescence lifetime data, that there are two distinct microscopice nvironments in some imidazolium ILs. [15] Although we believe that LFR spectroscopy is more suitable for structurale lucidation, because it can interrogate aw ider variety of ILs (whether liquid or solid at room temperature)w ithout the need for fluorescent probes, our conclusion presented above could be tested by the fluorescencemethod in future studies.…”
Section: (D)mentioning
confidence: 94%
“…[11,15,[46][47][48][49] Shaw et al used fluorescence correlation spectroscopy (FCS) to study N-alkyl-N-methylpyrrolidiniumN Tf 2 with different alkyl chain lengths. [11,15,[46][47][48][49] Shaw et al used fluorescence correlation spectroscopy (FCS) to study N-alkyl-N-methylpyrrolidiniumN Tf 2 with different alkyl chain lengths.…”
Section: (D)mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the authors concluded that the difference of the diffusion coefficients originates from subtle packing effects and not from inter-molecular interactions. Applying dye rhodamine 6G as tracer solute, a fast and a slow diffusion process were observed in pyrrolidinium TFSI-based ILs [60]. The respective fluorescence correlation spectroscopy study comprised ILs of various alkyl chain lengths.…”
Section: Charge Transport and Diffusionmentioning
confidence: 99%